Post Vaccination Surveillance of Pneumococcal Serotypes and Their Antimicrobial Susceptibility Profile Among Children Under Five in Accra, Ghana - Tettey, E.Y. (University of Ghana, 2017)
Background: In May 2012, Ghana introduced the PCV-13 as part of the routine childhood immunization programme with a view to mitigate the burden of pneumococcal disease among children under five. Vaccination though effective, creates a selection pressure that may lead to serotype replacement or capsular switching. This necessitates the need to perform post vaccination surveillance studies in areas where the PCV-13 has been introduced in order to ascertain current knowledge of serotype distribution necessary to evaluate vaccine efficacy. Aim: The aim of the study was to determine the antimicrobial susceptibility patterns and serotype distribution post PCV-13 vaccination in Accra, Ghana. Methodology: The research was a cross-sectional study involving seven randomly selected schools and 410 respondents in the Accra Metropolis of the Greater Accra region of Ghana. Informed consent was obtained from parents of the under-five year old children before a nasopharyngeal swab was taken. Identification and characterisation of S. pneumoniae was done based on methods described by the WHO. Results: Pneumococcal carriage prevalence among the study participants was 64.9%. Penicillin non-susceptibility prevalence was 26.7% with an intermediate resistance of 24.8% and full resistance of 1.9%. Trimethoprim-Sulphamethozaxole showed the highest resistance prevalence of 78.6% and Erythromycin showed the lowest prevalence of 16.7%. All isolates were susceptible to ceftriaxone and levofloxacin. Out of the 111/266 serotyping results, the three most dominant serotypes were; 23B (16.1%), 23F (9.7%) and 19F (7.5%). Conclusion: Pneumococcal carriage was observed in more than half of the study population characterised by reduction in the prevalence of penicillin non-susceptible Streptococcus pneumoniae. Non-PCV-13 serotype (23B) predominates in carriage and this serotype is associated with high MDR. PCV-13 failed to eliminate serotype 23F and 19F.
Keywords: pneumoniae; nasopharyngeal; Immunization; children